Pleiotropic effects of statins in the diseases of the liver - Janicko, Martin (World J Gastroenterol, 2016)
Statins are a class of molecules that inhibit HMG CoA reductase. They are usually prescribed as a lipid lowering medication. However, there is accumulating evidence that statins have multiple secondary effects both related and unrelated to their lipid-lowering effect. This narrative review of the literature aims to provide the reader with information from clinical studies related to the effect of statin and statins’ potential use in patients with liver diseases. In patients with advanced liver disease due to any etiology, statins exhibit an antifibrotic effect possibly through the prevention of hepatic sinusoidal microthrombosis. Two randomized controlled trials confirmed that statins decrease hepatic vein pressure gradient in patients with portal hypertension and improve the survival of patients after variceal bleeding. Lower rates of infections were observed in patients with cirrhosis who received statin treatment. Statins decrease the risk of hepatocellular carcinoma (HCC) in patients with advanced liver disease in general but particularly in patients with chronic hepatitis B and C. Statins in patients with chronic hepatitis C likely increase the virological response to the treatment with pegylated interferon and ribavirin and have the potential to decrease the rate of fibrosis. Finally, data from randomized controlled trials also confirmed that the addition of statin prolongs the survival of patients with advanced HCC even more than sorafenib. Statins are a very promising group of drugs especially in patients with liver disease, where therapeutic options can often be limited. Some indications, such as the prevention of re-bleeding from esophageal varices and the palliative treatment of HCC have been proven through randomized controlled trials, while additional indications still need to be confirmed through prospective studies.